Kombinasi BAP dan NAA untuk Media Perbanyakan Nanas Varietas Smooth Cayenne, Toboali in Vitro - Dahniar, Nia; Elvavina, Pepi (Agrotechnology Research Journal, 2022)
Toboali pineapple variety is a smooth cayenne variety because it contains high antioxidants in the form of vitamins A and C. In addition, it is a source of citric and malic acids, substances that can be used to enhance the taste of the fruit. Pineapple is a plant that is propagated with vegetative organs such as suckers, slips, and crowns. However, conventional propagation has a low propagation rate. Tissue culture is an in vitro technique used in the rapid propagation of plants and in large quantities to meet the needs of cultivation and research. The selection of regeneration media is very influential on the development of plants in tissue culture. This study aimed to obtain the optimal media combination with BAP and NAA in the regeneration of Smooth Cayenne pineapple (Toboali) in vitro for mass propagation of seedlings and genetic engineering research. This study used 6 levels of BAP, namely 0, 1, 2, 3, 4, 5 mg.L-1 and 4 levels of NAA, namely 0, 1, 2, 3 mg.L-1. The treatment used was a combination of BAP and NAA as many as 24 treatments with 3 replications. The best pineapple regeneration medium for mass plant propagation in this study was BAP 3 mg.L-1 without NAA media which produced the highest shoots of 17.33 shoots per explant at 12 week after planting. The best pineapple regeneration medium for genetic engineering research was a combination BAP 3 mg.L-1 and NAA 2 mg.L-1 media which produced 18.33 shoots per explant from embryogenic callus.